New species from a ‘lost world’: Sulawesidrobia (Caenogastropoda, Tateidae) from ancient Lake Matano, Sulawesi, Indonesia - Haase, Martin; von Rintelen, Thomas; Harting, Britta; Marwoto, Ristiyanti; Glaubrecht, Matthias (European Journal of Taxonomy, 2023)
Five new species of freshwater gastropods of the tateid genus Sulawesidrobia are described from the ancient Lake Matano on Sulawesi, Indonesia: S. wilsoni sp. nov., S. carsonae sp. nov., S. ehrlichi sp. nov., S. crutzeni sp. nov., and S. dinersteini sp. nov. The descriptions were based on shell morphology, anatomy as well as phylogenetic analysis using DNA sequence data of a fragment of the mitochondrial cytochrome oxidase I. All three suits of characters were included into the diagnoses. The new species formed a clade with two species from Lake Towuti, but separate from already known species from Lake Matano. The species were discovered between 2003 and 2005. However, not a single specimen of Sulawesidrobia was found when several sites were revisited in 2018 and 2019. This may be a consequence of the release of South American flowerhorn cichlid fish into the lake, in combination with heavy eutrophication of the once ultra-oligotrophic lake. It seems likely that several populations or even entire species of Sulawesidrobia in Lake Matano may be extinct. The species names given reflect this by acknowledging important conservationists.